Zika virus vaccines: immune response, current status, and future challenges. (August 2018) - Richner, Justin M; Diamond, Michael S
Highlights: B and T cell-mediated adaptive immune responses inhibit ZIKV in animal models. Early phase clinical trials in humans have demonstrated safety and immunogenicity. ZIKV vaccines may need to consider potential enhancement of DENV infection and GBS. Abstract : Zika virus (ZIKV) is the most recent mosquito-transmitted virus to cause a global health crisis following its entrance into a naïve population in the Western Hemisphere. Once the ZIKV outbreak began investigators rapidly established small and large animal models of pathogenesis, developed a number candidate vaccines using different platforms, and defined mechanisms of protection. In this review, we characterize the adaptive immune response elicited by ZIKV infections and vaccines, the status of ongoing clinical trials in humans, and discuss future challenges within the field.